Modern therapy of AMD - Stankiewicz, Andrzej; Figurska, Małgorzata (Przewodnik Lekarza/Guide for GPs, 2010)
Reactive oxygen forms play an important role in pathogenesis of many eye diseases, especially age-related macular degeneration (AMD), which affecting the central part of retina. AMD has two major forms: the dry type and wet type. Although wet type comprises only 15% of AMD, it is responsible for 90% of severe visual impairment in all cases. The antioxidants, especially vitamins E, C, carotenoids, zinc, polyunsaturated fatty acids are believed to offer protection against AMD and progression to advanced study - choroidal neovascularization. Lutein and zeaxanthin are two major carotenoid components of human macular pigment in the retina. They act effectively as blue-light filter and limit oxidative stress. Lutein is found in higher concentrations away from the fovea, which is in the center of the macula, while zeaxanthin concentrates closer to the fovea. Some dietary lutein appears to be converted to a non-dietary form of zeaxanthin (meso-zeaxanthin). The results of clinical subjects demonstrated, that supplementation with 6-14 mg lutein daily would increase macular pigment density. Historically in treatment of wet AMD we usually used radiation therapy, laser photocoagulation or surgical procedures. Now is the time for pharmacological approaches such as photodynamic therapy with Visudyne and anty-VEGF factors. Based on knowledge that VEGF factors are responsible for development and progression of CNV and on the success of anti-angiogenic therapies in the treatment of tumors anty VEGF A drugs are using as therapies for wet AMD. Intravitreal ranibizumab injections have FDA and EMEA recommendations for wet AMD treatment, because Lucentis is the first drug for intraocular use, which offers patients with wet AMD the opportunity to maintain and improve vision.